2012
DOI: 10.1016/j.jaac.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Early Behavioral Intervention Is Associated With Normalized Brain Activity in Young Children With Autism

Abstract: Objective A previously published randomized clinical trial indicated that a developmental behavioral intervention, the Early Start Denver Model (ESDM), resulted in gains in IQ, language, and adaptive behavior of children with autism spectrum disorder. This report describes a secondary outcome measurement from this trial, EEG activity. Method Forty-eight 18- to 30-month-old children with autism spectrum disorder were randomized to receive the ESDM or referral to community intervention for 2 years. After the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
434
0
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 643 publications
(464 citation statements)
references
References 28 publications
10
434
0
20
Order By: Relevance
“…This is unfortunate considering a recent report that gamma activity in the first 3 years of life is significantly predictive of enhancements in and development of language, cognition, and shifting attention (Benasich et al 2008), and other reports that gamma reflects long-range neural synchronization and connectivity (Engel et al 2001;Varela et al 2001), all of which have been noted to be negatively affected in ASD (Mundy et al 1990;Wing 1981;Just et al 2012). Regardless, the present study, in addition to Dawson et al (2012) and several others (Bolte et al 2006;Faja et al 2012;Russo et al 2010), provides mounting evidence that neural activity in ASD is responsive to socialbehavioral intervention across the lifespan.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…This is unfortunate considering a recent report that gamma activity in the first 3 years of life is significantly predictive of enhancements in and development of language, cognition, and shifting attention (Benasich et al 2008), and other reports that gamma reflects long-range neural synchronization and connectivity (Engel et al 2001;Varela et al 2001), all of which have been noted to be negatively affected in ASD (Mundy et al 1990;Wing 1981;Just et al 2012). Regardless, the present study, in addition to Dawson et al (2012) and several others (Bolte et al 2006;Faja et al 2012;Russo et al 2010), provides mounting evidence that neural activity in ASD is responsive to socialbehavioral intervention across the lifespan.…”
mentioning
confidence: 54%
“…Even though these interventions were brief and conducted with adults, the studies found that brain activity changed in response to the social training. A recent study found increased EEG activity to faces in a group of young children with autism who had been enrolled in early, intensive intervention (Dawson et al 2012). Another study found increased efficiency of brainstem responses to sound after children with ASD completed an auditory intervention (Russo et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable behavioral tests and neural markers of prediction may serve as early assays of these abilities in infants at risk and also be useful as tools to monitor the effectiveness of therapeutic interventions (as demonstrated in ref. 110).…”
Section: Resultsmentioning
confidence: 99%
“…In the treatment of autism, use of intensive early behavioral intervention, such as the Early Start Denver Model (ESDM) has been shown to improve developmental and social outcome in addition to normalization of the EEG abnormalities compared to those treated with community behavioral interventions (28). Such intervention is also recommended in young children with FXS both with and without autism or the PWP (29,30).…”
Section: Treatmentmentioning
confidence: 99%